2022
DOI: 10.1002/advs.202104883
|View full text |Cite
|
Sign up to set email alerts
|

Arrowhead Composite Microneedle Patches with Anisotropic Surface Adhesion for Preventing Intrauterine Adhesions

Abstract: Biomedical patches are considered as a promising strategy to help tissue repair and regeneration, prevent tissue adhesion, and reduce neighboring friction. Here, novel arrowhead composite microneedle patches (MNPs) are presented with anisotropic surface adhesion and growth factor encapsulation using a heterogeneous template replication approach for endometrium repair and intrauterine adhesions (IUAs) prevention. The arrowhead structures bring about interlocking between the microneedle (MN) tips and tissues, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…In particular, when the GelMA concentration reached 30%, each needle of MN could withstand a compression force of more than 0.2 N, which was sufficient for the successful puncture of the endometrium. [32] After placing the MN patch to rat uterine tissue, the MN tips could penetrate and insert into the endometrium (Figure 2f and Figure S2b, Supporting Information). Moreover, histopathological damage was not observed in major organs after the MN patch was placed to rat uterus compared with the normal control, suggesting the safety of GelMA in vivo (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, when the GelMA concentration reached 30%, each needle of MN could withstand a compression force of more than 0.2 N, which was sufficient for the successful puncture of the endometrium. [32] After placing the MN patch to rat uterine tissue, the MN tips could penetrate and insert into the endometrium (Figure 2f and Figure S2b, Supporting Information). Moreover, histopathological damage was not observed in major organs after the MN patch was placed to rat uterus compared with the normal control, suggesting the safety of GelMA in vivo (Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“… GelMA Arrays: Height: Shape: conical Strength: 0.3 ​N/needle CeO 2 nanozyme, stem cell antioxidant CeO 2 loaded base removed excessive ROS; Hydrogel needles improved stem cell activity, targeting efficiency and dwell time. [ 152 ] Arrowhead needles: GelMA; Base: bottom layer was N-acryloyl glycinamide (NAGA), top layer was PEGMA Arrays: Height: 760 ​μm Shape: Arrowhead Strength: 0.2 ​N/needle bFGF The arrowhead needles allowed MNs steadily adhering to the tissues and released growth factors; Backing layer prevented tissue adhesions [ 153 ] GelMA, Arrays: Height: 600 ​μm Shape: conical Strength: 0.2 ​N/needle Lactoferrin, human endometrium-derived adventitial cells Cells could rapidly form more biologically active three-dimensional cell spheres within the micropores surrounding the needles. Lactoferrin inhibited bacterial infections [ 154 ] …”
Section: Mns For Istrmentioning
confidence: 99%
“…The prevalence of intrauterine adhesions, a troublesome gynecological disease that poses a signicant risk to women's reproductive health, is one of the most pressing issues facing gynecologists today. [1][2][3][4][5] Human amniotic membrane (hAM) is an ideal material with great potential to prevent postoperative adhesion because of its natural biocompatibility and unique properties, such as self-contained stem cells, antibacterial properties, and exibility. Clinical studies have demonstrated that hAM can treat moderate and severe intrauterine adhesions with specic feasibility and safety benets, as the stem cells in hAM could effectively promote the repair of endometriosis.…”
Section: Introductionmentioning
confidence: 99%